Three notions of pluralism in public space - Thiebaut, Carlos (Estudios de Filosofía, 2008)
What I would like to argue, from the outset, is that our perception or our concept of pluralism is decisive for understanding the public space and that unit of agency that he called, with Rawls, the Social Union - or the social union of social unions, for being more faithful to its concept. The central hypothesis that will guide my reflection is what we will conceive, how it is and how it should be the public space according to our conceptions of what makes people different, diverse and that, in turn, different conceptions of that diversity entail various notions of what public space is like and what its role and structure should be and how it should be regulated by law.